2022
DOI: 10.1111/jcmm.17495
|View full text |Cite
|
Sign up to set email alerts
|

Molecular feature of neutrophils in immune microenvironment of muscle atrophy

Abstract: Homeostasis in skeletal muscle is sustained by the balance of functional and physical interactions between muscle and myofibre microenvironment. Various factors, such as ageing, disuse and denervation, tip the balance and induce skeletal muscle atrophy. Skeletal muscle atrophy, which involves complex physiological and biochemical changes, is accompanied by adverse outcomes and even increased mortality. Multiple studies have investigated the role of neutrophils in atrophied skeletal muscles; however, neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Neutrophils are the first line of defense of the immune system against fungal and bacterial infections under physiological conditions. The diversity of their individual activities and participation in BPs (such as NETs) play a critical role in inflammatory responses, overall immune coordination, and disease development [19]. Many studies have shown that neutrophils and their migration and infiltration may lead to major signaling events in skeletal muscle atrophy; however, neutrophil invasion into muscles is still controversial to some extent [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are the first line of defense of the immune system against fungal and bacterial infections under physiological conditions. The diversity of their individual activities and participation in BPs (such as NETs) play a critical role in inflammatory responses, overall immune coordination, and disease development [19]. Many studies have shown that neutrophils and their migration and infiltration may lead to major signaling events in skeletal muscle atrophy; however, neutrophil invasion into muscles is still controversial to some extent [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Spaceflight is known to induce immune dysregulation 60,61 and the immune system also plays a role in mediating the skeletal muscle response to disuse and recovery. [62][63][64][65] The baseline immune dysfunction in A/J mice could have been exacerbated by SM and led to the particularly sensitive response of A/J to SM. This finding suggests that immune dysfunction experienced during spaceflight could increase the magnitude of skeletal muscle loss and that enhancing the strength of the immune system could attenuate skeletal muscle loss during spaceflight, though further investigation is needed to confirm this link.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle-localized neutrophils are considered to release inflammatory cytokine, proteases, and free radicals, leading to exacerbated muscle atrophy ( 18 , 19 ). Furthermore, we found NETs were prominent in muscle on neutrophil-peaked day 14, suggesting that NETs may be associated with muscle atrophy and weakness.…”
Section: Discussionmentioning
confidence: 99%